Antimalarial activity of Malaysian plectranthus amboinicus against plasmodium berghei - Ramli, Norazsida; Syed Ahmad, Pakeer Oothuman; Sayed Ahmed, Hassan Mohamed Elhady; Bakhtiar, M. Taher (Wolters Kluwer Health, 2014)
Context: Malaria is a mosquito‐borne disease caused by parasitic protozoa from the genus of Plasmodium. The protozoans have developed resistance against many of current drugs. It is urgent to find an alternative source of new antimalarial agent. In the effort to discover new antimalarial agents, this research has been conducted on Plectranthus amboinicus. Aims: This study was conducted to evaluate the toxicity and antiplasmodial properties of P. amboinicus. Materials and Methods: Acute oral toxicity dose at 5000 mg/kg was conducted to evaluate the safety of this extract. Twenty mice were divided into control and experimental group. All the mice were observed for signs of toxicity, mortality, weight changes and histopathological changes. Antimalarial activity of different extract doses of 50, 200, 400 and 1000 mg/kg were tested in vivo against Plasmodium berghei infections in mice (five mice for each group) during early, established and residual infections. Results: The acute oral toxicity test revealed that no mortality or evidence of adverse effects was seen in the treated mice. The extract significantly reduced the parasitemia by the 50 (P = 0.000), 200 (P = 0.000) and 400 mg/kg doses (P = 0.000) in the in vivo prophylactic assay. The percentage chemo‐suppression was calculated as 83.33% for 50 mg/kg dose, 75.62% for 200 mg/kg dose and 90.74% for 400 mg/kg dose. Body weight of all treated groups; T1, T2, T3 and T4 also showed enhancement after 7 days posttreatment. Statistically no reduction of parasitemia calculated for curative and suppressive test. Conclusion: Thus, this extract may give a promising agent to be used as a prophylactic agent of P. berghei infection.